Vivências sobre investigação para a construção do raciocínio estatístico no ensino fundamental - Costa, Lucimelc Alves (2023)
The present study refers to the master's thesis allocated to the research line of Information, communication and interaction technology applied to the teaching of Science and Mathematics, of the Postgraduate Program in Teaching of Science and Mathematics, at the University of Passo Fundo. The research deals with an applied dissertation of a qualitative and quantitative nature, which is justified by the use of research teaching as a tool to encourage students to think and construct problem situations to help in the educational process, since the early years of Elementary School, with the insertion of interactive activities proposed in a textbook, with games in which children will be constructors of their own knowledge, which provides opportunities for meaningful, effective and lasting learning. This may lead the student to realize that statistical knowledge is important for their life in society and will be useful in helping them understand the world in which they live. The proposal to use research-based teaching encourages students to explore, develop strategies, raise hypotheses and conjectures, test, debate and apply mathematical ideas. The aim is to reflect on the pedagogical practices of multipurpose teachers when teaching Statistics, based on the guidelines of the National Curricular Parameters and the National Common Curricular Base, as well as reflecting on the proposal of textbooks regarding investigative experiences. In relation to methodological paths, a bibliographical research was carried out using scientific works as a source focusing on statistical teaching in Basic Education. In addition, playful material was created, which served as a reference to support all work with the teacher. As a theoretical reference, the research sought support in sociointeractionism, from the perspective of Lev Semenovich Vygotsky, in which the diverse use of teaching resources, with the mediation of the teacher and others, contributes to the construction of knowledge, socialization and interaction of the student. The educational product developed, available at https://educapes.capes.gov.br/handle/capes/742160, is a paradidactic book for students and teachers, aimed at statistical teaching, which seeks to involve the student in investigative activities and direct the teacher with strategies that mediated the construction of statistical reasoning. The application of the educational product, in turn, occurred through a didactic sequence, with students in the 3rd year of Elementary School, from a public school in the city of Gama, Federal District. The research result will be organized and analyzed, during and after the process, with activities carried out in the classroom and through a logbook, seeking to report the contributions that teaching through investigation and experimentation will promote in the development of statistical reasoning.